DUKUNGAN PT UNILEVER INDONESIA TERHADAP PARIS AGREEMENT UNTUK MENCAPAI NET ZERO EMISSION (NZE) MELALUI PROGRAM THE UNILEVER COMPASS - Putri, Viona Adlin; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Paris Agreement is established by the UN on December 12th, 2015 as an international environmental regime that focuses on the issue of climate change in realizing Net Zero Emissions which was agreed upon by 195 parties at COP21 in Paris. To realize Net Zero Emission, real action is needed to significantly reduce climate risks and impacts from all stakeholders, as is done by PT Unilever Indonesia in supporting the Paris Agreement through C2ES. This research will look at why PT Unilever Indonesia contributed to implementing the Paris Agreement through the Unilever Compass program. This research uses international regime theory and group level analysis. This theory explains the reason an actor participates in carrying out an international regime, namely it is based on Rational-choice which is a condition where an actor follows a regime because it analyzes and considers long-term impacts that can influence an actor's strategy. These considerations include safety, calculation and normative factors. The research method used is an explanatory qualitative method with data collection techniques obtained from literature studies. Results showed that PT Unilever Indonesia contributed to implementing the Paris Agreement in realizing Net Zero Emission through efforts to increase energy and air efficiency and waste utilization. The reason why PT Unilever supports the Paris Agreement is because there are considerations in analyzing long-term impacts, namely first as anticipation to gain a sense of security from various risks in the form of environmental risk, social risk and economic risk. Second, calculate the impact of external factors in the form of consumer and investor attraction, as well as technological development. Third, there is a normative factor which contains all the norms and laws that are the standards for implementing the Paris Agreement. Keywords: PT Unilever Indonesia, Paris Agreement, International Environmental Regime, Climate Change, MNC